The Effect of Project Based Learning Model on Learning Interest of Vocational Students in Surakarta - Sari, Nofri Novita; Budiyanto, Cucuk Wawan; Siyamtiningtyas, Yuliyani (Faculty of Teacher Training and Education Universitas Sebelas Maret Surakarta, 2024)
The background of the study was to determine the effect of Project Based Learning model on learning interest of vocational students in Surakarta. The purpose of this study is to increase the learning interest of vocational students by applying the Project Based Learning model. This research uses qualitative methods with methods for gathering data through surveys and observations. The research subjects were vocational students and teachers of public vocational schools in Surakarta. Which consisted of 36 students and 1 subject teacher. The results showed that 75% of students liked the learning process with the Project Based Learning model, while 25% liked other learning models. From these results it can be seen that the majority of students like the Project Based Learning model. So, it can be said that Surakarta's vocational students' interest in learning can be piqued by the Project Based Learning approach.